The interaction between academic stress and self-control in predicting psychological well-being - Balan Rathakrishnan; Azizi Yahaya; Soon Singh Bikar Singh; Mohd Dahlan A. Malek; Muhammad Idris Bullare @ Bahari; Ismail Maakip; Voo, Peter Su Kiong; Noor Hassline Mohamed (Asia Pacific Academy of Science Pte. Ltd., 2023)
This study was conducted to identify the influence of academic stress and self-control on the psychological wellbeing of university students in the Kota Kinabalu, Malaysia campus. Besides that, gender ethnicity and location (oncampus and off-campus) have been compared according to academic stress, self-control and psychological well-being. This study uses a quantitative method in which 320 university students were involved. The research questionnaire consists of the Perception of Academic Stress Scale (PAS), the Sense of Control Scale and the Psychological Wellbeing (PWB) Scale were used as instruments of this study. This study found that academic stress and self-control are direct predictors of the psychological well-being of university students during the COVID-19, with beta value, the study findings showed (Beta = –0.18, R² = 0.056, p < 0.05) and self-control (Beta = 0.17, R² = 0.052, p < 0.05). Based on this indicates, academic stress contributed (5.6%) and self-control (5.2%) to the psychological well-being of university students during the COVID-19 pandemic. This is due to the academic stress from the aspect of workload that is given during the online teaching and learning sessions. Therefore, university student needs to give importance to self-control and other recreational activity for them to be psychologically happy during the COVID-19 pandemic. With high self-control, students can manage their academic stress and increase their psychological well-being.